Trophic ecology in an anchialine cave: A stable isotope study. - Brenda Durán; Fernando Álvarez (PLoS ONE, 2025)
The analysis of carbon and nitrogen stable isotopes (δ13C and δ15N) has been widely used in ecology since it allows to identify the circulation of energy in a trophic network. The anchialine ecosystem is one of the less explored aquatic ecosystems in the world and stable isotope analysis represents a useful tool to identify the routes through which energy flows and to define the trophic niches of species. Sampling and data recording was conducted in one anchialine cave, Cenote Vaca Ha, near the town of Tulum, Quintana Roo, Mexico, where seven stygobitic species endemic to the anchialine caves of the Yucatan Peninsula, plus sediment, water and vegetation samples were analyzed to determine what the main nutrient sources are. We compared our results with two previous studies, one conducted in the same cave and another one from a cave in the same area, both based on the same seven species which are widely distributed in the area. Our study revealed: a) that despite a certain amount of variation in the δ13C and δ15N values of the species through time, both seasonally and interannually, the anchialine isotopic niche is much conserved; b) through contribution models we propose what are the most probable food sources for the studied species and the results confirm previous trophic classifications; and c) that the shrimp Typhlatya pearsei presents very negative δ13C values, suggesting their consumption of bacterial sources consistent with a chemosynthetic origin of organic matter. The implications of the new findings show a very stable ecosystem with the shrimp Typhlatya pearsei, as the key species to link chemosynthetic microbial production of organic matter to the anchialine trophic web.